HUBUNGAN DUKUNGAN KELUARGA DENGAN INTERAKSI SOSIAL PADA PENDERITA KUSTA DI DUSUN SUMBER GLAGA DESA TANJUNG KENONGO KECAMATAN PACET KABUPATEN MOJOKERTO - Wicaksono, Arif; Miftachur Rifqi, Chaidar (JURNAL KEPERAWATAN SEHAT, 2015)
Family support is crucial used by individuals to solve the problem, an effective family will help people to get good social interaction. Family support has been linked to an individuals response in the face of leprosy. The purpose of the study was to determine Relationships With Family Support Social Interaction In Hamlet source Glagah Tanjung Kenongo District Pacet Mojokerto. Design analytical research with cross sectional approach. Existing population leper families in the hamlet of the village of Tanjung Kenongo source Glagah Mojokerto District Pacet many as 180 people to obtain a sample of 45 people were taken by cluster random sampling. Independent variable and the dependent variable family support social interactions in patients with leprosy. The data were taken using a questionnaire. Having collected the data processing performed and followed by statistical test chi square test using SPSS version 17.0. research results show ρ (1,000) > α (0.05), so that H0is accepted it means there is no relationship between family support social interactions in patients with leprosy. In order to further enhance social interaction in the community of lepers against the family should further increase its support for leprosy patients so that they are able to interact socially with both and can plunge into society.Keywords:family support, social interaction, people with leprosy